English Premier League, Spanish La Liga and Italys Series A what's different? - Sarmento, H.; Pereira, A.; Matos, N.; Campanico, J.; Anguera, M. T.; Leitao, J. (International Journal of Performance Analysis in Sport, 2013)
Our study aimed to understand which aspects are most important by coaches in the characterization of the three best European Football Leagues (English Premier League, Spains La Liga and Italýs Seriés A). The sample included 8 expert high-performance Portuguese First League football coaches. Semi-structured interviews were carried out and data were analysed through Content Analysis.